2006
DOI: 10.1027/1015-5759.22.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Emotion Regulation Questionnaire (CERQ)

Abstract: The main purpose of this study was to validate a French version of the Cognitive Emotion Regulation Questionnaire (CERQ). A sample of 224 young adults completed the French translation of the CERQ and the Beck Depression Inventory II. Exploratory and confirmatory factor analyses showed that a nine-factor model also explained the data collected with the French version. Internal reliability scores for each strategy ranged from .68 to .87. As in the original version, we found that the emotion regulation strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
102
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(127 citation statements)
references
References 14 publications
(25 reference statements)
9
102
0
16
Order By: Relevance
“…Nine cognitive emotion regulation strategies are distinguished by the CERQ on theoretical and empirical bases, each referring to people's cognitions or thoughts after they have experienced threatening or stressful events [4], was the Þ rst paper in which the nine strategies were described: Since its development, the CERQ has been translated into several languages. These languages include among others: Dutch [8], English [4], Spanish [9], Italian [10], Turkish [11,12], Persian [13,14], Chinese [15], French [16], German [17], Hungarian [18] and Romanian [19]. One consistent Þ nding across these studies is that good psychometric properties are observed for the instrument.…”
Section: Introductionsupporting
confidence: 49%
“…Nine cognitive emotion regulation strategies are distinguished by the CERQ on theoretical and empirical bases, each referring to people's cognitions or thoughts after they have experienced threatening or stressful events [4], was the Þ rst paper in which the nine strategies were described: Since its development, the CERQ has been translated into several languages. These languages include among others: Dutch [8], English [4], Spanish [9], Italian [10], Turkish [11,12], Persian [13,14], Chinese [15], French [16], German [17], Hungarian [18] and Romanian [19]. One consistent Þ nding across these studies is that good psychometric properties are observed for the instrument.…”
Section: Introductionsupporting
confidence: 49%
“…Furthermore, the validity and original factor structure of the CERQ have been successfully replicated across samples in several countries (Domínguez-Sánchez et al, 2013;Jermann et al, 2006;Martin & Dahlen, 2005;Tuna & Bozo, 2012;Zhu et al, 2008).…”
mentioning
confidence: 94%
“…There is some support for the distinction between adaptive (e.g., reappraisal) and maladaptive (e.g., rumination) cognitive emotion regulation strategies (Aldao, 2012;Domínguez-Sánchez et al, 2013;Jermann et al, 2006;Werner & Gross, 2010, cf. Campos, Walle, Dahl, & Main, 2011Tuna & Bozo, 2012).…”
mentioning
confidence: 99%
“…This measure comprises 9 subscales: Self-blame, Blaming others, Rumination, Catastrophizing, Putting into Perspective, Positive Refocusing, Positive Reappraisal, Acceptance and Refocus on planning. The first four subscales refer to less adaptive emotion regulation strategies, while the last five one refer to more adaptive strategies [15].…”
Section: Cognitive Emotion Regulation Questionnaire (Cerq)mentioning
confidence: 99%
“…The objective of this study was to test the relation between selfdiscrepancies evaluated by the Self-Discrepancy Questionnaire and different self-related dimensions: 1-self-consciousness, to evaluate whether the self-discrepancies are related to higher attention to private or public dimensions of the self ; 2-affects evaluated both by the positive and negative affect scale [12] and by the Beck Depression Inventory [13], that should be related to higher self-discrepancies; 3-emotional regulations strategies, as assessed by the CERTS [14], that evaluates repetitive thinking and the CERQ [15], that evaluates more complex modes of emotion regulation, as the development high levels of self-discrepancies is expected to be related to the emergence of nonadaptive self-regulation strategies as suggested by Baumeister [7]; 4-Alcohol craving and alcohol intake that may express a specific mode of non-adaptive regulation strategy and especially in individuals with high self-consciousness.…”
Section: Introductionmentioning
confidence: 99%